C1-Pathways in Methyloversatilis universalis FAM5: Genome Wide Gene Expression and Mutagenesis Studies - Nathan M. Good; Andrew Lamb; David A. C. Beck; N. Cecilia Martinez-Gomez; Marina G. Kalyuzhnaya (Microorganisms, 2015)
Methyloversatilis universalis FAM5 utilizes single carbon compounds such as methanol or methylamine as a sole source of carbon and energy. Expression profiling reveals distinct sets of genes altered during growth on methylamine vs methanol. As expected, all genes for the N-methylglutamate pathway were induced during growth on methylamine. Among other functions responding to the aminated source of C1-carbon, are a heme-containing amine dehydrogenase (Qhp), a distant homologue of formaldehyde activating enzyme (Fae3), molybdenum-containing formate dehydrogenase, ferredoxin reductase, a set of homologues to urea/ammonium transporters and amino-acid permeases. Mutants lacking one of the functional subunits of the amine dehydrogenase (ΔqhpA) or Δfae3 showed no growth defect on C1-compounds. M. universalis FAM5 strains with a lesion in the H4-folate pathway were not able to use any C1-compound, methanol or methylamine. Genes essential for C1-assimilation (the serine cycle and glyoxylate shunt) and H4MTP-pathway for formaldehyde oxidation showed similar levels of expression on both C1-carbon sources. M. universalis FAM5 possesses three homologs of the formaldehyde activating enzyme, a key enzyme of the H4MTP-pathway. Strains lacking the canonical Fae (fae1) lost the ability to grow on both C1-compounds. However, upon incubation on methylamine the fae1-mutant produced revertants (Δfae1R), which regained the ability to grow on methylamine. Double and triple mutants (Δfae1RΔfae3, or Δfae1RΔfae2 or Δfae1RΔfae2Δfae3) constructed in the revertant strain background showed growth similar to the Δfae1R phenotype. The metabolic pathways for utilization of methanol and methylamine in Methyloversatilis universalis FAM5 are reconstructed based on these gene expression and phenotypic data.